Interorbital singlet pairing in Sr2RuO4: A Hund's superconductor - Käser, Stefan; Strand, Hugo U.R.; Wentzell, Nils; Georges, Antoine; Parcollet, Olivier; Hansmann, Philipp (Physical Review B, 2022)
We study the superconducting gap function of Sr2RuO4. By solving the linearized Eliashberg equation with a correlated pairing vertex extracted from a dynamical mean-field calculation we identify the dominant pairing channels. An analysis of the candidate gap functions in orbital and quasiparticle band basis reveals that an interorbital singlet pairing of even parity is in agreement with experimental observations. It reconciles in particular the occurrence of a two-component order parameter with the presence of line nodes of quasiparticles along the c axis in the superconducting phase. The strong angular dependence of the gap along the Fermi surface is in stark contrast to its quasilocality when expressed in the orbital basis. We identify local interorbital spin correlations as the driving force for the pairing and thus reveal the continuation of Hund's physics into the superconducting phase.
CRIS-Team Scopus Importer:2022-04-29